PROGRAM PEMBERDAYAAN PEDAGANG KAKI LIMA TERDAMPAK PANDEMI COVID 19 DI KAWASAN WISATA UMBUL MADIUN DALAM RANGKA PENGUATAN KETAHANAN EKONOMI - Rohmatiah, Ahadiati; Iswati, Retno; Pratiwi, Dian; Lukito, Martin (UNIVERSITAS PGRI MADIUN, 2022)
Abstract. Tourism is a sector that supports the economy of a region which has a major influence on other sectors. Tourism is one of the sectors most affected by the Covid-19 pandemic. This impact is increasingly seen with the existence of Large-Scale Social Restrictions (PSBB) and PPKM (Enforcement of Restrictions on Community Activities) by the Government. At the Umbul Tourism Park located in Glonggonng village, Dolopo District, Madiun Regency, there are 49 street vendors at Umbul Tourism Park or Madiun Umbul Square who depend on selling their lives at tourist sites and are no longer selling. The solution provided by the Merdeka Madiun University service team for street vendors in Madiun Umbul Square who were affected by the Covid-19 pandemic was to empower partners, namely by: 1) Strengthening economic resilience for partners due to the Covid-19 Pandemic; 2) improvement of partner's standard of living through new production business; 3) increasing cooperation among members with the principles of sharing and collaborating; 4) Managing waste into salable products; 5) Counseling on the importance of layout and hygiene for business premises; 6) Opening market access for production results outside the tourist park area. To achieve these goals, empowerment programs are carried out: 1) Counseling on the principles of sharing and collaborating; 2) Counseling on the importance of layout and hygiene of business premises; 3) Training on making knitting masks and connectors; 4) Training on worm maintenance and vermicompost production; 5) Training on making organic liquid fertilizer from household waste.Abstrak. Pariwisata merupakan sektor penopang ekonomi suatu wilayah yang memberikan pengaruh besar bagi sektor-sektor lainnya. Pariwisata merupakan salah satu sektor paling terdampak dari pandemi Covid-19. Dampak tersebut semakin terlihat dengan adanya Pembatasan Sosial Berskala Besar (PSBB) dan PPKM (Pemberlakuan Pembatasan Kegiatan Bermasyarakat) oleh Pemerintah. Di Taman Wisata Umbul yang terletak di desa Glonggonng, Kecamatan Dolopo, Kabupaten Madiun, terdapat 49 pedagang kaki lima Taman Wisata Umbul atau Madiun Umbul Square yang menggantungkan hidup dari berjualan di lokasi Wisata dan kini sudah tidak berjualan lagi. Solusi yang diberikan oleh tim pengabdian Universitas Merdeka Madiun untuk pedagang kaki lima Madiun Umbul Square yang terdampak pademi Covid -19 adalah pemberdayaan mitra, yakni dengan cara : 1) Menguatkan ketahanan ekonomi bagi mitra akibat Pandemi Covid-19; 2) Meningkatkan taraf hidup mitra melalui usaha produksi baru; 3) Meningkatkan kerja sama antar anggota dengan prinsip berbagi dan berkolaborasi; 4) Mengelola sampah menjadi produk bernilai jual; 5) Penyuluhan pentingnya tata letak dan higienitas bagi tempat usaha; 6) Membuka akses pasar bagi hasil produksi di luar wilayah taman wisata. Untuk mencapai tujuan tersebut, program pemberdayaan yang dilakukan : 1) Penyuluhan Prinsip berbagi dan berkolaborasi; 2) Penyuluhan pentingnya tata letak dan higienitas tempat usaha; 3) Pelatihan pembuatan masker dan konektor rajut; 4) Pelatihan pemeliharaan cacing dan produksi kascing; 5) Pelatihan pembuatan pupuk cair organik dari limbah rumah tangga.